Trends and Future Research in Face Masks Performance against Acute Respiratory Infections (ARI): A Scientometrics Analysis - Reza Pourbabaki; Mojtaba Emkani; Zabiholah Damiri; Moslem Alimohammadlou; Mehdi Jahangiri (Journal of Health Sciences and Surveillance System)
Background: One of the major causes of morbidity and mortality among infectious diseases is acute respiratory infections. Masks are often recommended as proper personal protective equipment for preventing the spread of respiratory infections. This study aims to provide valuable insights into historical and current trends in research on mask performance, with a particular focus on hotspots and trend studies.Methods: In this Systematic Review, relevant studies on face mask efficacy were retrieved from the Web of Science (data extracted on July 15, 2023). The selected articles were analyzed using VOSviewer, R (Bibliometrix package), and Tableau tovisualize geographic distributions, conduct bibliometric analyses, and map research trends across countries, institutions, keywords, and journals.Results: The number of articles published in 2020 and 2021 has increased significantly. Overall, 1193 papers were identified, published by authors from 88 countries. According to literature citations, the journal “PloS ONE” published the most research on the topic. Fabric mask filtration performance was evaluated in the two documents with the highest total link strength. With the outbreak of COVID-19 around the world, studies were more focused on fit tests and filtration of surgical, medical, and N95 masks, indicating that researchers are exploring the effectiveness of masks to ensure the effectiveness of face masks.Conclusion: This study suggests potential knowledge gaps regarding the effectiveness of face masks, so future research should focus on challenges such as uncertain efficacy and fitness.